Tolerance against ischemic neuronal injury can be induced by volatile anesthetics and is inducible NO synthase dependent - Kapinya, Krisztián; Löwl, Diana; Fütterer, Carsten Dietmar; Maurer, Martin H.; Waschke, Klaus F.; Isaev, Nikolaj K.; Dirnagl, Ulrich (Stroke, 2002)
Background and Purpose: We tested whether volatile anesthetics induce neuroprotection that is maintained for a prolonged time.Methods— Rats were pretreated for 3 hours with 1 minimal anesthetic concentration of isoflurane or halothane in normal air (anesthetic preconditioning [AP]). The animals were subjected to permanent middle cerebral artery occlusion (MCAO) at 0, 12, 24, or 48 hours after AP. Halothane-pretreated animals were subjected to MCAO 24 hours after AP. Histological evaluation of infarct volumes was performed 4 days after MCAO. Cerebral glucose utilization was measured 24 hours after AP with isoflurane. Primary cortical neuronal cultures were exposed to 1.4% isoflurane for 3 hours. Oxygen-glucose deprivation (OGD) was performed 24 hours after AP. Injury was assessed 24 hours later by measuring the release of lactate dehydrogenase into the medium 24 hours after OGD. Results: Isoflurane anesthesia at 0, 12, and 24 hours before MCAO or halothane anesthesia 24 hours before MCAO significantly reduced infarct volumes (125±42 mm3, P=0.024; 118±51 mm3, P=0.008; 120±49 mm3, P=0.009; and 121±48 mm3, P=0.018, respectively) compared with control volumes (180±51 mm3). Three hours of isoflurane anesthesia in rats did not have any effect on local or mean cerebral glucose utilization measured 24 hours later. Western blot analysis from cortical extracts of AP-treated animals revealed an increase of the inducible NO synthase (iNOS) protein beginning 6 hours after AP. The iNOS inhibitor aminoguanidine (200 mg/kg IP) eliminated the infarct-sparing effect of AP. In cultured cortical neurons, isoflurane exposure 24 hours before OGD decreased the OGD-induced release of lactate dehydrogenase by 49% (P=0.002). Conclusions: Pretreatment with volatile anesthetics induces prolonged neuroprotection in vitro and in vivo, a process in which iNOS seems to be critically involved.
Gesehen am 28.05.2021